PENGARUH GOOD CORPORATE GOVERNANCE DAN UKURAN PERUSAHAAN TERHADAP KINERJA PERUSAHAAN (Studi empiris pada perusahaan yang terdaftar di BEI 2010) - Iqbal Bukhori; Rahardja Rahardja (Diponegoro Journal of Accounting, 2012)
This study aims to examines the effect of good corporate governance and the company size to companiesperformance in Indonesia. The factors tested in this study is the size of the board of directors and the size of the board commissioner as aninternal mechanisms of corporate governance and company size. Corporate performance is measured by CFROA. Data collection using random sampling method to the companies listed in Indonesia Stock Exchange in 2010. There was 160 companies used as sampel. The method of analysis of this study used multiple regression. These results of the study indicates that there is no significant effect between internal mechanisms of corporate governance to company performance. Similarly, no significant effect of firm size on corporate performance. This means that the internal mechanisms of corporate governance and firm size had no effect on corporate performance